The Normative Core of Relational Stakeholder Strategies: Explaining Open Buyer-Supplier Relations in the Context of the Amazon Rainforest - Lazzarini, Sérgio ca. 20./21. Jh. (Business ethics quarterly, 2026)
While from an instrumental perspective stakeholder relations can promote sustained competitive advantage, normative arguments underscore the importance of morally informed principles, especially when relational strategies have uncertain future outcomes and are prone to imitation. This study investigates how such instrumental and normative views can be complementary based on the case study of Natura, a cosmetics company procuring natural inputs from the Amazon rainforest via supplier relations that are open to multiple parties, including competitors. The research shows that Natura developed and reinforced a morally informed normative core specifying how the company and its managers should act. This resulted in a long-term commitment to the open relational strategy, especially when future outcomes were largely uncertain, which in turn promoted emergent instrumental gains via deepened relational attachments and substantive stakeholder engagement. Importantly, the company's controlling shareholders strongly influenced the normative core, thus underscoring the importance of identifying key shareholders and their values.